Asthma as a Protective Factor against COVID-19 Infection: A Narrative Literature Review - Monica Bil Geni; Deddy Herman; Dessy Mizarti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Asthma and COPD comorbidities are expected to exacerbate the clinical manifestations of COVID-19. However, many reported studies show that asthmatic patients infected with COVID-19 do not show severe clinical manifestations, and some are asymptomatic. This literature review aimed to describe COVID-19 in asthmatic patients along with the hypothesis that asthma is a protective factor against COVID-19 infection. Systemic corticosteroids have been shown to reduce the death/mortality rate in patients who are hospitalized due to COVID-19 infection. This is possibly due to the suppression of the immune system against a hyperinflammatory state which can result in further damage from SARS-CoV-2 infection. Mucus hypersecretion, which is one of the hallmarks of asthma, can prevent the SARS-CoV-2 virus from reaching the distal lung and can protect the lungs from pathological processes. The secreted mucus is rich in glycoproteins, such as MUC5AC, which act as the first line of defense against infection. Mucus hypersecretion in asthmatic patients may prevent SARS-CoV-2 from penetrating far enough to gain access to type-2 alveolar cells, which are the cells that predominantly express ACE2 in the lungs. In conclusion, comorbid asthma in patients infected with COVID-19 does not cause adverse clinical manifestations to appear, but on the contrary, it will have a protective effect on patients.